2013
DOI: 10.4161/auto.24543
|View full text |Cite
|
Sign up to set email alerts
|

Lumenal peroxisomal protein aggregates are removed by concerted fission and autophagy events

Abstract: We demonstrated that in the yeast Hansenula polymorpha peroxisome fission and degradation are coupled processes that are important to remove intra-organellar protein aggregates. Protein aggregates were formed in peroxisomes upon synthesis of a mutant catalase variant. We showed that the introduction of these aggregates in the peroxisomal lumen had physiological disadvantages as it affected growth and caused enhanced levels of reactive oxygen species. Formation of the protein aggregates was followed by asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…When we were preparing our manuscript, Manivannan et al published a paper showing that Dnm1 and Vps1 are important for the removal of intra-peroxisomal protein aggregates and pexophagy in Hansenula polymorpha and Saccharomyces cerevisiae. 18 Here, we extend that analysis by providing evidence indicating how the fission machinery is recruited to the peroxisomes to facilitate peoxphagy.…”
Section: Discussionmentioning
confidence: 88%
“…When we were preparing our manuscript, Manivannan et al published a paper showing that Dnm1 and Vps1 are important for the removal of intra-peroxisomal protein aggregates and pexophagy in Hansenula polymorpha and Saccharomyces cerevisiae. 18 Here, we extend that analysis by providing evidence indicating how the fission machinery is recruited to the peroxisomes to facilitate peoxphagy.…”
Section: Discussionmentioning
confidence: 88%
“…For example, treating Arabidopsis seedlings with tunicamycin, which blocks protein glycosylation and triggers the unfolded protein response, promotes autophagy of the endoplasmic reticulum (Liu et al, 2012). In addition, accumulation of protein aggregates in the peroxisome matrix is accompanied by heightened pexophagy in H. polymorpha (Manivannan et al, 2013). It is tempting to speculate that the oxidized or obsolete matrix proteins that accumulate as lon2 seedlings age trigger pexophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using two model systems have shed light on this. In the first study, the fate of intraperoxisomal aggregates of a mutant form of catalase was followed in H. polymorpha 139 . This study identified a pathway, whereby aggregates are sequestered into a distinct subpopulation of peroxisomes (FIG.…”
Section: Peroxisome Differentiationmentioning
confidence: 99%
“…The images in parts e and f are reproduced, with permission, from REF. 139 © (2013) Landes Bioscience. The image in part g courtesy of Sanjiban Banerjee and Marilyn Parsons, Seattle Biomedical Research Institute, Seattle, Washington, USA.…”
Section: Figurementioning
confidence: 99%